AN ANALYSIS OF STUDENTS' PERCEPTIONS ON TEACHING SPEAKING STRATEGIES AT THE EIGHT GRADERS OF SMP YP SUNAN DALEM GUMENO - Mazidah, Eva Nur; Sabella, Nadia (Faculty of Teacher Training and Education, English Department, UNISKA, Kediri, 2024)
This research was conducted to find out (1) the strategies used by the teacher and (2) students’ perception on teaching speaking strategies at the eighth graders of SMP YP Sunan Dalem Gumeno 2023. This research design was descriptive qualitative research. The subject of this research was the teacher and the students at the eighth graders of SMP YP Sunan Dalem Gumeno 2023, in here there are one English teacher and twenty six students. The data were obtained through questionnaire and interview. The results showed that the teacher has various strategies used to teach speaking in class such as discussion, drilling, and games. The results of students' perceptions also showed good responses to the strategies used by the teacher to teach speaking. They could get many benefits from the strategies used by the teacher as they are more confident in speaking English, they can convey their ideas, they easily remember new vocabulary and they easily understand the material presented by the teacher.